Działalność państwa i samorządu terytorialnego w świetle koncepcji działań zbiorowych ekonomii instytucjonalnej - Noga, Marian (State and territorial autonomy activities in terms of collective action concepts in institutional econom, 2005)
The state and the territorial autonomy interfere in economy processes due to overall disorder which is unwanted by the society. This is a basic hypothesis presented in this article. The author proves its correctness by comparison analysis of different economy trends’ collective action concepts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 56-63